Biological functions at high pressure: transcriptome response of Shewanella oneidensis MR-1 to hydrostatic pressure relevant to Titan and other icy ocean worlds - Malas, Judy; Russo, Daniel C.; Bollengier, Olivier; Malaska, Michael J.; Lopes, Rosaly M. C.; Kenig, Fabien; Meyer-Dombard, D'Arcy R. (Frontiers in Microbiology, 2024)
High hydrostatic pressure (HHP) is a key driver of life's evolution and diversification on Earth. Icy moons such as Titan, Europa, and Enceladus harbor potentially habitable highpressure environments within their subsurface oceans. Titan, in particular, is modeled to have subsurface ocean pressures ≥ 150 MPa, which are above the highest pressures known to support life on Earth in natural ecosystems. Piezophiles are organisms that grow optimally at pressures higher than atmospheric (0.1 MPa) pressure and have specialized adaptations to the physical constraints of high-pressure environmentsup to ~110 MPa at Challenger Deep, the highest pressure deep-sea habitat explored. While non-piezophilic microorganisms have been shown to survive short exposures at Titan relevant pressures, the mechanisms of their survival under such conditions remain largely unelucidated. To better understand these mechanisms, we have conducted a study of gene expression for Shewanella oneidensis MR-1 using a high-pressure experimental culturing system. MR-1 was subjected to short-term (15 min) and long-term (2 h) HHP of 158 MPa, a value consistent with pressures expected near the top of Titan's subsurface ocean. We show that MR-1 is metabolically active in situ at HHP and is capable of viable growth following 2 h exposure to 158 MPa, with minimal pressure training beforehand. We further find that MR-1 regulates 264 genes in response to short-term HHP, the majority of which are upregulated. Adaptations include upregulation of the genes argA, argB, argC, and argF involved in arginine biosynthesis and regulation of genes involved in membrane reconfiguration. MR-1 also utilizes stress response adaptations common to other environmental extremes such as genes encoding for the cold-shock protein CspG and antioxidant defense related genes. This study suggests Titan's ocean pressures may not limit life, as microorganisms could employ adaptations akin to those demonstrated by terrestrial organisms.